Modelo explicativo da exclusão social de usuárias de drogas com base no preconceito e nos estereótipos de gênero - Medeiros, Katruccy Tenório (2018)
The prejudice against women still remains as a phenomenon of impact on society, especially when these are seen as "Swerve". Women to be viewed while drug users constitute a target group of social exclusion, explained by the perception of threat, by moralizing and by gender stereotypes. From a multimétodo approach, were conducted four studies whose overall objective was to create an explanatory model of social exclusion of drug users based on prejudice and gender stereotypes. In 1 Study, qualitative, two surveys were conducted; the first, in the Brazilian context, using 100 college students, sought to know and compare the stereotypes of women with those of women believed to be drug users, by means of the technique of free association of Words (TALP) and analyzed with the assistance IRAMUTEQ software, with the Woman-inducing stimulus which was associated with maternal-family content, and stimulating Woman drug User-connected to the contents of abandonment and isolation; and the second research, comparative and cross-cultural character Brazil-Portugal, using 100 participants from each country and with use of TALP, sought to compare the inductors Woman-which remained the maternal content in both countries, and drug-using Women/ woman addict, describing expressiveness for the Brazilians, and the Portuguese, pathological content. 2 study, correlational character and using of 208 students, aimed to create the measure: female stereotypes against the Use of Drugs (EEFMUD); and adapt and validate the following instruments: Perception of Threat to Women Drug Users (EPAMUD); Scale of Moralization front women drug Users (EMMUD); Scale of intended Social contact front women drug Users (EICSMUD); and scale of Social exclusion to Women Drug Users (EESMUD). The results showed good indicators validity and accuracy. Already the 3 Study, gathered evidence of acceptability of the measures employed in the previous study, using new testing with 200 students. The results ensured good psychometric indicators. Already the study 4, sought to scale the predictive effect of stereotypes, the perception of threat, of moralizing and intention of social contact in social exclusion, using a sample of 400 students. The results showed a simple mediation model statistically significant (λ = 0.55, 90% CI = 0.51/0.03 p < 0.01), through the prediction of Stereotypes λ = 0.21 (90% CI = 0.17/0.03) p 0.01, perception < Threat λ = 0.53 (90% CI = 0.50; 0.01 and 0.04 p < Moraliz λ = 0.15 action (90% CI = 0.08; 0.02) 0.01, in variable < Social exclusion, from the intention to Contact Social.